Comparison of turbulence models in near wake of transport plane C-130H fuselage - Pang, Samuel Kheng Hong (2013)
This paper presents a computational fluid dynamics analysis of the delayed detached eddy simulation–shear-stress transport on a 1:16 scale simplified C-130H fuselage model in flight conditions and with a closed cargo ramp to observe the turbulent-flow structures that evolve behind its empennage region. The results of which are also compared against already existing x-vorticity plots of the delayed detached eddy simulation–Spalart–Allmaras with rotation and curvature correction. With vorticity magnitude of 750 rotations∕s, the delayed detached eddy simulation–shear-stress transport is shown to display a lot more detail in terms of the formation and unsteadiness of the upsweep and detached vortices. The simulations are performed with the finite volume solver Cobalt with up to 64 processors on a high-performance computer.